N-Glycosylation Regulates the Trafficking and Surface Mobility of GluN3A-Containing NMDA Receptors - Skrenkova, Kristyna; Lee, Sanghyeon; Lichnerova, Katarina; Kaniakova, Martina; Hansikova, Hana; Zapotocky, Martin; Suh, Young Ho; Horak, Martin (Frontiers in Molecular Neuroscience, 2018)
N-methyl-D-aspartate receptors (NMDARs) play critical roles in both excitatory neurotransmission and synaptic plasticity. NMDARs containing the nonconventional GluN3A subunit have different functional properties compared to receptors comprised of GluN1/GluN2 subunits. Previous studies showed that GluN1/GluN2 receptors are regulated by N-glycosylation; however, limited information is available regarding the role of N-glycosylation in GluN3A-containing NMDARs. Using a combination of microscopy, biochemistry, and electrophysiology in mammalian cell lines and rat hippocampal neurons, we found that two asparagine residues (N203 and N368) in the GluN1 subunit and three asparagine residues (N145, N264, and N275) in the GluN3A subunit are required for surface delivery of GluN3A-containing NMDARs. Furthermore, deglycosylation and lectin-based analysis revealed that GluN3A subunits contain extensively modified N-glycan structures, including hybrid/complex forms of N-glycans. We also found (either using a panel of inhibitors or by studying human fibroblasts derived from patients with a congenital disorder of glycosylation) that N-glycan remodeling is not required for the surface delivery of GluN3A-containing NMDARs. Finally, we found that the surface mobility of GluN3A-containing NMDARs in hippocampal neurons is increased following incubation with 1-deoxymannojirimycin (DMM, an inhibitor of the formation of the hybrid/complex forms of N-glycans) and decreased in the presence of specific lectins. These findings provide new insight regarding the mechanisms by which neurons can regulate NMDAR trafficking and function.